Molecular properties of octenyl succinic esters of mechanically activated Indica rice starch1. Issue 5 (7th January 2013) - Zhang, Zhengmao; Zhao, Siming; Xiong, Shanbai
Abstract Indica rice starch was mechanically activated and then esterified by octenyl succinic anhydride (OSA). The molecular properties of the OSA‐starch were investigated by gel permeation chromatography, high performance size‐exclusion chromatography, FTIR spectroscopy, 1H NMR, 13C NMR spectroscopy. Modification by OSA could increase the molecular size or hydrodynamic volume of starch. As shown in FTIR spectrum of OSA‐starch, the relative intensity of characteristic peaks at 1724 and 1572/cm increased as the degree of substitution (DS) increased, which confirmed the esterification between OSA and starch. It can be concluded from the analysis of 1H NMR, and 13C NMR that the esterification between mechanically activated Indica rice starch and OSA should have occurred at 2‐OH, 3‐OH, and 6‐OH of glucose residue. As increasing DS decreased the relative intensity of the peak of chemical shift of 2‐OH in the 1H NMR spectrum of OSA‐starch, 2‐OH was possible the main substitution position.